The Effectiveness of Cancer Pain Management in a Tertiary Hospital Outpatient Pain Clinic in Thailand: A Prospective Observational Study - Suratsawadee Wangnamthip; Skaorat Panchoowong; Carolina Donado; Kimberly Lobo; Pimporn Phankhongsap; Pinyo Sriveerachai; Pramote Euasobhon; Pranee Rushatamukayanunt; Sahatsa Mandee; Nantthasorn Zinboonyahgoon; Charles B. Berde (Pain Research and Management)
Context. In a previous retrospective study, cancer pain management was effective in 47.5% of a cohort assessed after 3 months in a pain clinic at Siriraj Hospital. New guidelines were established, including a multidisciplinary approach, availability of pain interventions, and palliative care referral. Objectives. The objective was to examine the effectiveness of the updated approach. Methods. With IRB approval, outpatients with cancer were enrolled from January to December 2018. Assessments were recorded at baseline and three consecutive visits (BL, FU1, FU2, and FU3), including Numerical Rating Scale (NRS), the Brief Pain Inventory (BPI), the Edmonton Symptom Assessment System (ESAS), side effects, and analgesic use. The primary outcome was a favorable response, defined as an NRS decrease more than 30% or NRS <4. Secondary outcomes included trends over time in BPI, ESAS, side effects, and analgesic use. Pain response predictors at FU3 were analyzed using logistic regression. Results. Among 150 patients, 72 (48%) completed follow-ups. Of these, 61% achieved a favorable response at FU3. Pain interference diminished at all visits relative to baseline (p<0.05). Median morphine equivalent daily dosage (MEDD) at BL was 20 mg/day, with a statistically significant, but clinically modest increase to 26.4 mg/day at FU3. Radiation therapy during pain care was a predictor of pain responders. Conclusion. The current Siriraj multidisciplinary approach provided effective relief of pain and stabilization of other cancer-related symptoms. Radiation therapy during pain care can be used to predict pain outcomes. Ongoing improvement domains were identified and considered in the context of cultural, economic, and geographic factors.